MORAL KERJA GURU DI SMK NEGERI 6 KOTA PADANG - Aditya Julivan Pratama (Jurnal Bahana Manajemen Pendidikan, 2015)
This research is motivated from the observation of the author at SMK Negeri 6 of Padang which showed that is still not running as it should be. Research question posed is how the morale of teachers working at SMK Negeri 6 Padang City in terms of: Morale, Discipline of work, and responsibility. This is a descriptive study with a population of 93 people. The Sample was taken with porpotional random sampling technique with a sample of 30 people. Data collection tool that is used is a questionnaire scale linkert. The results showed the overall morale of teachers at SMK Negeri 6 of Padang id in good categories with an average score of 3.58. Keyword : Working Morale